Microsurgical treatment of breast cancer-related lymphedema under contrast-enhanced ultrasound guidance: a case report and literature review - Zhao, Qiuchan; Huang, Xing; Chen, Weizhang; Xiao, Yi; Zhang, Jialing; Liu, Yujun; Liang, Rongkang; Liang, Zhongzeng (Frontiers in Oncology, 2025)
Lymphedema remains a chronic and challenging condition with limited curative options. Recent advances have expanded treatment strategies from comprehensive conservative management to microsurgical interventions, particularly lymphaticovenous anastomosis (LVA). LVA is a physiological surgical method in which functional lymphatic vessels are connected to nearby subdermal venules, enabling lymphatic fluid to bypass obstructed pathways and drain into the venous circulation. The success of LVA depends heavily on the accurate preoperative assessment and localization of functional lymphatic vessels. Contrast-enhanced ultrasound (CEUS) offers a valuable, non-invasive tool for identifying deep lymphatic channels, enabling dynamic evaluation of lymphatic contractility, peristalsis, and lymph flow. Furthermore, CEUS facilitates the identification of appropriately sized recipient veins, thereby reducing operative complexity and shortening surgical duration. We report a case of secondary upper limb lymphedema following breast cancer surgery, in which LVA was successfully performed under CEUS guidance using supermicrosurgical techniques.